Penerapan Model Pembelajaran Numbered Head Together (NHT) Untuk Meningkatkan Hasil Belajar SKI Materi Sejarah Beberapa Kerajaan Islam di Jawa, Sumatra dan Sulawesi - Denovia Denovia (AT-TA'DIB: JURNAL ILMIAH PRODI PENDIDIKAN AGAMA ISLAM, 2019)
The purpose of this research was to improve the learning outcomes of material SKI History of some Islamic kingdoms in Java, Sumatra and Sulawesi by applying the NHT Learning Model to Class IX-B Students of MTs Negeri 2 Simeulue. This research is Classroom Action Research which is carried out in the cycles and with stages of planning, action, observation, and reflection. The study was conducted in odd semester for three months starting from August 2017 to October 2017. Subjects in this research were students of class IX-B of MTs Negeri 2 Simeulue in the 2017/2018 school year which amounted to 18 students. Techniques for collecting data through observation and student learning tests. Data was analyzed using descriptive method. The results showed that: (1) Completeness of student learning outcomes in the pracycle is 50%, in the first cycle increased to 77.8% and in the second cycle also increased to 94.4%. (2) The teacher's activities in managing learning in the first cycle are classified as good, namely 3.5. In the second cycle, the ability of the teacher to manage learning has improved, which is better, which is 4.2 which is good. (3) The activities of students in the first cycle are classified as sufficient, namely 3.3. Then in the second cycle increased and good helped namely 4. Thus, it can be concluded that the learning outcomes of material SKI History Some Islamic kingdoms in Java, Sumatra and Sulawesi can be increased by applying the NHT Learning Model to class IX-B MTs Negeri 2 Simeulue.